Fatal Case of Rabies in a Captive White-Tailed Deer: A Case Report from Chiapas, Mexico - Moisés Armides Franco-Molina; Silvia Elena Santana-Krímskaya; Baltazar Cortés-García; Jorge Alejandro Sánchez-Aldana-Pérez; Oscar García-Jiménez; Jorge Kawas (Tropical Medicine and Infectious Disease, 2021)
Rabies is a fatal viral infection that causes enc ephalitis in warm-blooded animals, including humans. Dog-transmitted rabies is considered eradicated in Mexico; however, rabies is not being tested in livestock with neurological symptoms (one of the main manifestations of rabies disease). In this case report, we describe a rabies case in a white-tailed deer in the Santo Domingo ranch, in Catazajá, Chiapas, Mexico, where white-tailed deer are kept under captivity, and are meant for human consumption. This is the first report of a rabies case in white-tailed deer in Mexico. We also describe the challenges to obtain a rabies diagnosis and the lack of public health policies to ensure containment of the disease, as well as the lack of awareness among farmers in the area. One single confirmed case of rabies indicates that more animals are affected by the disease. The risk for human health and economical losses will remain unknown until rabies tests are routinely performed in animals that present neurological symptoms.